The Role of Character Development in Islamic Religious Education: An Islamic Values-Based Approach at one of the MAN Schools in South Sulawesi - Muh Idris (West Science Interdisciplinary Studies, 2023)
This research explores the pivotal role of character development within Islamic Religious Education (IRE) using an Islamic values-based approach in Madrasah Aliyah Negeri (MAN) schools situated in South Sulawesi. By investigating teachers' and students' perceptions and assessing the impact of the approach on character development, this study aims to contribute valuable insights into the significance of character education within the context of MAN schools. The research employs a mixed-methods approach, incorporating qualitative interviews and quantitative surveys to provide a comprehensive understanding of the topic. The findings underscore the interconnectedness of faith and ethics, revealing the positive influence of an Islamic values-based approach on students' moral growth.